2005
DOI: 10.1111/j.1365-2648.2004.03320.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported characteristics of women and men with intimate body piercings

Abstract: Understanding client rationale is not a necessary prerequisite for providing quality patient care; however, awareness of purposes and decision-making in intimate piercing can help nurses to be sensitive to client needs and plan appropriate health education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
83
1
21

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(109 citation statements)
references
References 38 publications
4
83
1
21
Order By: Relevance
“…In a study of 445 men with genital piercings, 53% reported having at least one complication post procedure [4]. Another study that surveyed 84 men and women with genital piercings found that 52% reported at least one health-related problem following their piercings [6]. These complications may be related to the piercing process itself, or the persistence of a foreign body in the tissue [19][20][21].…”
Section: Complicationsmentioning
confidence: 99%
See 4 more Smart Citations
“…In a study of 445 men with genital piercings, 53% reported having at least one complication post procedure [4]. Another study that surveyed 84 men and women with genital piercings found that 52% reported at least one health-related problem following their piercings [6]. These complications may be related to the piercing process itself, or the persistence of a foreign body in the tissue [19][20][21].…”
Section: Complicationsmentioning
confidence: 99%
“…The Victorian era had Prince Albert, Queen Victoria's husband, who allegedly wore a penile ring to secure his genitals to the right or left leg of the extremely tight pants he wore, as was the fashion of that period. Currently, the "Prince Albert" is reported to be the most popular style of penile ring [2,[4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations